2013
DOI: 10.5214/ans.0972.7531.200406
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neurophysiological and mri findings of patients with multiple sclerosis using oligoclonal band technique

Abstract: BackgroundThe correlation of oligoclonal bands (OCBs) and intrathecal IgG synthesis are not yet clear in multiple sclerosis (MS).PurposeIn this study, we investigated the OCB situation and IgG index, cranial and cervical magnetic resonance imaging (MRI) findings and also compared visual evoked potentials (VEP) and somatosensorial evoked potentials (SEP) in order to better understand the OCB pattern and pathogenesis.MethodsRetrospective study included 40 patients (19 male, 21 female, mean age 29 ± 4,24) with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(36 reference statements)
0
7
0
1
Order By: Relevance
“…Therefore, the detection of sub-clinical lesions of the visual pathway has become an important aspect in the assessment of newly diagnosed MS cases [ 38 , 39 ]. While electrophysiological examinations are not a part of the McDonald 2010 criteria, studies demonstrated that VEP latency combined with MRI could improve the accuracy of MS prediction [ 9 , 40 ]. Our results confirm that delayed VEP represent an additional risk factor for conversion to MS in OCB negative CIS patients with optic neuritis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the detection of sub-clinical lesions of the visual pathway has become an important aspect in the assessment of newly diagnosed MS cases [ 38 , 39 ]. While electrophysiological examinations are not a part of the McDonald 2010 criteria, studies demonstrated that VEP latency combined with MRI could improve the accuracy of MS prediction [ 9 , 40 ]. Our results confirm that delayed VEP represent an additional risk factor for conversion to MS in OCB negative CIS patients with optic neuritis.…”
Section: Discussionmentioning
confidence: 99%
“…It is the leading cause of disabilities in young adults. Although it does not have a limiting effect on survival, it is associated with the potential of development of disability over years, thus having significant socioeconomic outcomes [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…The association between CSF-OCB status and MRI features remains unclear. Previous studies on the MRI differences between OCB-positive and OCB-negative patients have been limited to traditional MRI parameters such as anatomical lesion locations or visually graded brain atrophy, and results have been inconsistent 13,14 . Thus, in this study, we explored the association between CSF-OCB status and advanced MRI metrics that are related to disease prognosis.…”
mentioning
confidence: 99%